Impact of administrative empowerment on the creativity of Algerian start-ups - El Amine Abdel Hafidi, Mohammed; Ilimi, Chihab; Benfattoum, Fathi (International journal of economic perspectives, 2024)
The present study aims to highlight the role of the impact of administrative empowerment on improving creativity within Algerian start-ups. The study population consisted of a few Algerian start-ups with a total of 70 questionnaire forms distributed and 50 valid forms of them were collected. The study found that there is an impact with statistical significance at the level (α ≤0.05). Dimensions of empowerment (employee training, effective communication and teamwork) on improving creativity among Algerian Start-Ups. It was also found that there were no statistically significant variances at Sig Level (α ≤0.05) between workers’ tendencies toward creativity enhancement, which can be attributed to the functional variables (Age and experience). Study recommended applying modern administrative concepts such as the principle of enabling participation, the formation of working groups and teamwork and administrative decision making, also preparing the working environment in a way that supports the empowerment by adopting cooperation and coordination between administrations, divisions, groups and individuals, and by working to enable decentralization, delegation of power and participation of subordinates in decision-making, and finally by working on establish an effective system of financial and intangible incentives for employees.